Renal Involvement in Multisystem Inflammatory Syndrome in Children: Not Only Acute Kidney Injury - Alessandra Meneghel; Valentina Masenello; Fiorenza Alfier; Stefania Giampetruzzi; Camilla Sembenini; Giorgia Martini; Francesca Tirelli; Davide Meneghesso; Francesco Zulian (MDPI AG, 2023)
Kidney involvement has been poorly investigated in SARS-CoV-2 Multisystem Inflammatory Syndrome in Children (MIS-C). To analyze the spectrum of renal involvement in MIS-C, we performed a single-center retrospective observational study including all MIS-C patients diagnosed at our Pediatric Department between April 2020 and May 2022. Demographic, clinical, pediatric intensive care unit (PICU) admission's need and laboratory data were collected at onset and after 6 months. Among 55 MIS-C patients enrolled in the study, kidney involvement was present in 20 (36.4%): 13 with acute kidney injury (AKI) and 7 with isolated tubular dysfunction (TD). In eight patients, concomitant AKI and TD was present (AKI-TD). AKI patients needed higher levels of intensive care (PICU: 61.5%, p < 0.001; inotropes: 46.2%, p = 0.002; second-line immuno-therapy: 53.8%, p < 0.001) and showed lower levels of HCO3- (p = 0.012), higher inflammatory markers [neutrophils (p = 0.092), PCT (p = 0.04), IL-6 (p = 0.007)] as compared to no-AKI. TD markers showed that isolated TD presented higher levels of HCO3- and lower inflammatory markers than AKI-TD. Our results indicate a combination of both pre-renal and inflammatory damage in the pathogenesis of kidney injury in MIS-C syndrome. We highlight, for the first time, the presence of tubular involvement in MIS-C, providing new insights in the evaluation of kidney involvement and its management in this condition.